2017
DOI: 10.12968/bjon.2017.26.6.340
|View full text |Cite
|
Sign up to set email alerts
|

Children and young people with diabetes: recognition and management

Abstract: Diabetes mellitus (type 1) is an autoimmune condition leading to absolute insulin deficiency resulting in hyperglycaemia and its associated manifestations. It is the most common type of diabetes seen in children, characterised by the 4Ts (toilet, thinner, thirsty, tired). The signs and symptoms can sometimes be non-specific and a delay or missed diagnosis may be catastrophic to the health of the child. Children with an established diagnosis of diabetes often present to the health service with issues such as hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
0
9
0
4
Order By: Relevance
“…School nurses are often called to aide children in checking their blood glucose, administering insulin, and assessing for complications (hypoglycemia and hyperglycemia), as well as providing and reinforcing diabetes education. Including education on the importance of sleep, sleep habits, and asking children how they are sleeping may be first steps in opening up a wider dialogue that also can include parents (Hamilton, Knudsen, Vaina, Smith, & Paul, 2017).…”
Section: Implications For School Nursesmentioning
confidence: 99%
“…School nurses are often called to aide children in checking their blood glucose, administering insulin, and assessing for complications (hypoglycemia and hyperglycemia), as well as providing and reinforcing diabetes education. Including education on the importance of sleep, sleep habits, and asking children how they are sleeping may be first steps in opening up a wider dialogue that also can include parents (Hamilton, Knudsen, Vaina, Smith, & Paul, 2017).…”
Section: Implications For School Nursesmentioning
confidence: 99%
“…Previous studies found that young adults with T1D reported poor mental health, such as anxiety, depression, and stress (Mellerio et al, 2015; Rathbone & Prescott, 2017). Patients with T1D may suffer difficulties in performing frequent blood glucose monitoring, active insulin‐dose titration tailored to carbohydrate intake, and physical activities, thereby causing psychological distress and a decrease in mental health (Hamilton et al, 2017). Evidence supports reminders of blood glucose monitoring, carbohydrate intake education, and engagement in insulin treatment being beneficial for people with T1D (Baretić et al, 2018; Wangberg et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Jis gali varginti įvairaus amžiaus vaikus, netgi kūdikius (American Diabetes Association, 2017). Cukrinis diabetas vaikams nustatomas esant labai aukštam gliukozės kiekiui kraujyje (Dabelea, Stafford, Mayer-Davis, 2017;Hamilton, Knudsen, Vaina, 2017).…”
Section: įVadasunclassified